EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PENGELOLAAN LINGKUNGAN PESISIR DAN LAUT DI DESA TANJUNG SELOKA KECAMATAN PULAU LAUT SELATAN KABUPATEN KOTABARU KALIMANTAN SELATAN - Hadi, Abdul; Amani, Mukhyar; Rahman, Basuki (Universitas Lambung Mangkurat, 2023)
Tanjung Seloka Village is one of many villages located in the coastal area of Kotabaru Regency, South Kalimantan. Because it is located on the coast, many people there work or have a livelihood in the field of marine products, from fishermen, collectors, and retailers, to fish traders in the market. In addition to being very far from the city center, this village is also not easily accessible due to road conditions that are not fully supported. This situation then affects many aspects of life in Tanjung Seloka Village, both educational, economic, social, and the environment in general. One of the problems that occur in Tanjung Seloka Village is the lack of public insight regarding applicable government regulations related to the management of coastal and marine areas, which may be due to problems of distance, access, and so that the government is lacking in providing socialization to the community.